Phytochemical Screening and Bioactive Properties of Juglans regia L. Pollen - Natalia Żurek; Karolina Pycia; Agata Pawłowska; Ireneusz Tomasz Kapusta (MDPI AG, 2022)
Pollen is one of the major by-products of the walnut tree, yet it is poorly investigated. Thus, the aim of this study was to investigate the total phenolics, flavonoids, antioxidant, anticancer potential, and polyphenol profile of pollen obtained from male Juglans regia flowers. A total of 24 phenolic compounds were identified in Juglans regia pollen and all of them were reported for the first time for this raw material. The content of polyphenols was 408.03 mg/100 g dry weight (dw) and the most abundant components were quercetin 3-O-sophoroside and 4',5,7-trihydroxy-3,6-dimethoxyflavone-7-O-beta-D-glucoside. The concentration of these compounds, as well as the total content of polyphenols and flavonoids, strongly determined the antioxidant and cytotoxic activity of Juglans regia pollen. Antioxidant action using the ABTS and CUPRAC methods had the values of 3.35 and 0.32 mmol TE/g dw, respectively. In turn, in the tests of chelating ability of ferrous ion, O2•− and OH− radical scavenging activity, of which the results were expressed as IC50, the values were equal to 335.01, 459.31, and 92.89 µg/mL, respectively. Among the six cancer cell lines, the strongest effect was demonstrated for Caco-2 (140.65 µg/mL) and MCF-7 (140.98 µg/mL) cells. The results provide valuable and previously unpublished data on the polyphenol composition and biological potential of Juglans regia pollen.